Association between breast milk intake at 9–10 months of age and growth and development among Malawian young children. Issue 3 (19th January 2018) - Kumwenda, Chiza; Hemsworth, Jaimie; Phuka, John; Ashorn, Ulla; Arimond, Mary; Maleta, Kenneth; Prado, Elizabeth L.; Haskell, Marjorie J.; Dewey, Kathryn G.; Ashorn, Per
Abstract: World Health Organization recommends exclusive breastfeeding for infants for the first 6 months of life, followed by introduction of nutritious complementary foods alongside breastfeeding. Breast milk remains a significant source of nourishment in the second half of infancy and beyond; however, it is not clear whether more breast milk is always better. The present study was designed to determine the association between amount of breast milk intake at 9–10 months of age and infant growth and development by 12–18 months of age. The study was nested in a randomized controlled trial conducted in Malawi. Regression analysis was used to determine associations between breast milk intake and growth and development. Mean ( SD ) breast milk intake at 9–10 months of age was 752 (244) g/day. Mean ( SD ) length‐for‐age z‐score at 12 months and change in length‐for‐age z‐score between 12 and 18 months were −1.69 (1.0) and −0.17 (0.6), respectively. At 18 months, mean ( SD ) expressive vocabulary score was 32 (24) words and median (interquartile range) skills successfully performed for fine, gross, and overall motor skills were 21 (19–22), 18 (16–19), and 38 (26–40), respectively. Breast milk intake (g/day) was not associated with either growth or development. Proportion of total energy intake from breast milk was negatively associated with fine motor (β = −0.18, p  = .015) but not other developmental scores in models adjusted for potential confounders. Among Malawian infants, neither breast milk intake nor percent of total energy intake from breast milk at 9–10 months was positively associated with subsequent growth between 12 and 18 months, or development at 18 months.